IDE Gene Polymorphism Influences on BPSD in Mild Dementia of Alzheimer's Type. (26th November 2008) - Sato, Noriko; Ueki, Akinori; Ueno, Hideo; Shinjo, Hidetaka; Morita, Yoshio
Abstract : Insulin degrading enzyme (IDE) degrades amyloidβ (Aβ ), which may inhibit the accumulation of Aβ in a brain affected with dementia of Alzheimer's type (DAT). A decrease in the activity of IDE results in changes in glucose utilization in the brain, which could affect the cognitive and psychiatric symptoms of DAT. We investigated a possible association of IDE gene polymorphism and the behavioral and psychological symptoms of dementia (BPSD) in mild DAT. The genotyping for IDE and apolipoprotein E (ApoE) was determined in 207 patients with mild DAT and 215 controls. The occurrence of BPSD was demonstrated using the Behavioral Pathology in Alzheimer's Disease Rating Scale (BEHAVE-AD). IDE gene polymorphism is unlikely to play a substantial role in conferring susceptibility to DAT, but it may be involved in the development of affective disturbance through the course of mild DAT, regardless of the presence of an ApoEε 4 allele. The present data could be the result of a small sample size. Further investigations using larger samples are thus required to clarify the correlation between IDE gene polymorphism, susceptibility to DAT, and emergence of BPSD.